NILAI KEPAHLAWANAN PADA FILM SALAHUDIN AL AYYUBI (SEMIOTIKA CHARLES SANDERS PEIRCE) - Nur Azizah, Fitria; Dayudin; Mardiansyah, Yadi (Universitas Hamzanwadi, 2025)
This study analyzes the values of heroism in the film Salahudin Al Ayyubi using Charles Sanders Peirce’s semiotic approach. Peirce’s semiotic theory divides signs into three main elements: Representamen (the sign itself), Object (what the sign represents), and Interpretant (the meaning derived from the sign). Using a qualitative analysis method, this study identifies visual and narrative symbols that represent heroism in the film. The analysis reveals five key heroic values reflected in the film: sacrifice, courage, responsibility, empathy, and justice. These values are represented through various visual signs, dialogues, and the actions of the main character, as well as events that depict the struggle to uphold justice and truth. The findings of this study indicate that Salahudin Al Ayyubi not only presents a historical and heroic narrative but also conveys profound moral messages through semiotic symbols. Furthermore, this research highlights the importance of semiotic analysis in understanding how heroic values are constructed and perceived by the audience. Thus, this study contributes to film studies and the interpretation of heroism in film media.